Socialization of The Islamic-Based Existencial Humanistic Approach in Preventing Fatherlessness and Motherlessness Among Prospective Spouses - Maulida Putri Utami, Maulida Putri Utami; Ummi Kalsum; Siti Azhara; Dela Zulfa Karimah Shofawati; Parhaen; Jarir Idris; Casmini; Irsyadunnas (Transformatif : Jurnal Pengabdian Masyarakat, 2025)
The increasing phenomenon of fatherlessness and motherlessness in Indonesia has a serious impact on the emotional and psychological development of children. This condition confirms the urgency of socialization of Islamic-based humanistic existential values for the among prospective spouses as a preventive strategy to instill a deep understanding of the role and responsibility of parents in building a harmonious family. This activity uses Participatory Action Research (PAR) method through socialization to 21 couples of among prospective spouses at Kua Kemantren Umbulharjo and Kua Kapanewon Depok. The process is implemented in four stages: planning, interactive implementation, collaborative reflection, and re-planning, with the active involvement of participants. The results of the activities showed a significant increase in knowledge, critical awareness, and readiness of participants to prevent fatherlessness and motherlessness. Changes in perception are evident from a deeper understanding of the causes, impacts, and prevention strategies, as well as a growing awareness of the importance of collaboration, effective communication, and a balanced distribution of roles within the family. This Program not only strengthens the readiness of the parenting role but also supports the sustainability of adaptive and meaningful community service.